Biofilm‐induced profiles of immune response gene expression by oral epithelial cells. (16th January 2019) - Ebersole, Jeffrey L.; Peyyala, Rebecca; Gonzalez, Octavio A.
Abstract : This study examined the oral epithelial immunotranscriptome response patterns modulated by oral bacterial planktonic or biofilm challenge. We assessed gene expression patterns when epithelial cells were challenged with a multispecies biofilm composed of Streptococcus gordonii, Fusobacterium nucleatum, and Porphyromonas gingivalis representing a type of periodontopathic biofilm compared to challenge with the same species of planktonic bacteria. Of the 579 human immunology genes, a substantial signal of the epithelial cells was observed to 181 genes. Biofilm challenged stimulated significant elevations compared to planktonic bacteria for IL32, IL8, CD44, B2M, TGFBI, NFKBIA, IL1B, CD59, IL1A, CCL20 representing the top 10 signals comprising 55% of the overall signal for the epithelial cell responses. Levels of PLAU, CD9, IFITM1, PLAUR, CD24, TNFSF10, and IL1RN were all elevated by each of the planktonic bacterial challenge vs the biofilm responses. While the biofilms up‐regulated 123/579 genes (>2‐fold), fewer genes were increased by the planktonic species (36 [ S gordonii ], 30 [ F nucleatum ], 44 [ P gingivalis ]). A wide array of immune genes were regulated by oral bacterial challenge of epithelial cells that would be linked to the local activity of innate and adaptive immune response components in the gingival tissues. Incorporating bacterial species into a structured biofilm dramatically altered the number and level of genes expressed. Additionally, a specific set of genes were significantly decreased with the multispecies biofilms suggesting that some epithelial cell biologic pathways are down‐regulated when in contact with this type of pathogenic biofilm.